The Elusive Gains from International Financial Integration - Gourinchas, Pierre-Olivier (IMF Working Papers; Working Paper ;, 2004)
Standard theoretical arguments tell us that countries with relatively little capital benefit from financial integration as foreign capital flows in and speeds up the process of income convergence. We show in a calibrated neoclassical model that conventionally measured welfare gains from this type of convergence appear relatively limited for developing countries. The welfare gain from switching from financial autarky to perfect capital mobility is roughly equivalent to a 1 percent permanent increase in domestic consumption for the typical non-OECD country. This is negligible relative to the welfare gain from a take-off in domestic productivity of the magnitude observed in some of these countries.